Glycosylation Reactions in the Synthesis of Flavonoid Glycosides - Sun, Jiansong; Laval, Stéphane; Yu, Biao (Synthesis, 2014)
An overview of flavonoid glycoside synthesis has been provided with an emphasis on the construction of the glycosidic linkages.1 Introduction2 Synthetic Tactics3 Synthesis of Flavonoid O-Glycosides3.1 Glycosylation with Glycosyl Bromides3.2 Glycosylation with Glycosyl Imidates3.3 Glycosylation with Glycosyl Esters3.4 Glycosylation with Glycosyl Fluorides3.5 Combined Application of Different Types of Glycosyl Donors4 Synthesis of Flavonoid C-Glycosides5 Synthesis of Flavonoid Mixed O,C-Glycosides6 Conclusion
Keywords: flavonoid glycoside; glycosylation; protecting group; glycosyl bromide; glycosyl fluoride; glycosyl imidate; glycosyl ortho-alkynylbenzoate